A produção de conhecimentos no serviço social: Entre a hegemonia do marxismo e a pós- modernidade - Galdino, Shellen Batista (2016)
This study analyzes the production of knowledge in Social Service in Brazil with respect to modernity and postmodernity. It is recognized that Marxism has become hegemonic in Social Work, however, from the 1970s occur profound changes in bourgeois sociability and capital worldwide, these changes have as a framework the crisis of capital and its consequences on the economy and culture. These changes put in evidence the paradigm hegemony of modern rationality with the establishment of a society called "postmodern" and "flexible accumulation". Thus, modern reason loses ground to the primacy of subjectivity, the ephemeral and methodological relativism, so, with the situation of crisis and defensive historical-critical perspective, there acirramentos disputes in the production of knowledge. In Social work, we analyzed that occur interference of postmodern thought, wether through syncretic / eclectic, neo-conservative or by that route "critical", but that interference is timid and that for an hour is sky and per hour is in exhaustion process.